2022
DOI: 10.1186/s13578-022-00762-1
|View full text |Cite
|
Sign up to set email alerts
|

Decoding ceRNA regulatory network in the pulmonary artery of hypoxia-induced pulmonary hypertension (HPH) rat model

Abstract: Background Hypoxia-induced pulmonary hypertension (HPH) is a lethal cardiovascular disease with the characteristic of severe remodeling of pulmonary vascular. Although a large number of dysregulated mRNAs, lncRNAs, circRNAs, and miRNAs related to HPH have been identified from extensive studies, the competitive endogenous RNA (ceRNA) regulatory network in the pulmonary artery that responds to hypoxia remains largely unknown. Results Transcriptomic p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…At present, in terms of mechanisms, circRNAs exert their function mainly through the following activities (Patop et al., 2019; Rong et al., 2022; Wang, Niu, et al., 2022): (a) serving as a competitive endogenous RNA (ceRNA) that is, circRNA absorbs miRNA in the cytoplasm to reduce the binding of miRNA to downstream target genes; (b) binding to related proteins in the cytoplasm; (c) acting as scaffolding proteins for protein–protein interactions and (d) combining with corresponding proteins in the nucleus, stabilizing them so that they are not easily degraded. In this study, circ‐ZNF236 and miR‐218‐5p were colocalized in the cytoplasm of SCAPs, as shown by nucleocytoplasmic separation and FISH assay results.…”
Section: Discussionmentioning
confidence: 99%
“…At present, in terms of mechanisms, circRNAs exert their function mainly through the following activities (Patop et al., 2019; Rong et al., 2022; Wang, Niu, et al., 2022): (a) serving as a competitive endogenous RNA (ceRNA) that is, circRNA absorbs miRNA in the cytoplasm to reduce the binding of miRNA to downstream target genes; (b) binding to related proteins in the cytoplasm; (c) acting as scaffolding proteins for protein–protein interactions and (d) combining with corresponding proteins in the nucleus, stabilizing them so that they are not easily degraded. In this study, circ‐ZNF236 and miR‐218‐5p were colocalized in the cytoplasm of SCAPs, as shown by nucleocytoplasmic separation and FISH assay results.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that this difference may be linked to posttranscriptional regulation, recognizing the inherent limitations in the cell model. In a study (48) involving hypoxia-induced pulmonary hypertension (HPH), miR205, miR-20a-5p, and miR-541 were predicted to target POSTN, and these microRNAs might compete with several lncRNAs and circRNAs for binding to POSTN. Whether POSTN exhibits certain post-transcriptional regulatory mechanisms in pulmonary fibrosis remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, high-throughput RNA sequencing has been widely used to explore novel mechanisms of PAH [ 6 , 43 ]. Especially, with the rapid development of single-cell sequencing, integrated bioinformatics analysis of microarray transcriptome and scRNA-seq, a newly-rising research method, has attracted researchers’ attention lately [ 44 ].…”
Section: Discussionmentioning
confidence: 99%